Stability of Droplets for the Three Dimensional Stochastic Ising Model (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
In this paper we study the evolution of the finite volume stochastic Ising model with magnetic field at very low temperatures starting from regular droplets, namely configurations on which all spins are -1 except those inside a parallelepiped.